EVOLUTION OF MONETARY POLICY FRAMEWORK IN INDIA SINCE INDEPENDENCE - Kumar, Praveen; Ranawat, Mahendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The monetary policy framework plays a major role in shaping the economic sphere of a country. The economic journey of India is self-evident due to the dynamic nature of monetary policy formulation and its implementation in response to the evolving economic conditions, internal and external to India. This paper gives a very comprehensive examination of the monetary policy framework evolution of India since the establishment of the RBI (Reserve Bank of India). Furthermore, the paper explores the pre-reform and post-reform characteristics of the monetary policy framework through pre-independence (1935 to 1947), after-independence & pre-reform periods (1947 to 1990) and post-reform period (1991 onwards). The paper also examines the various monetary policy frameworks including planned economic development, multiple indicator approach, flexible inflation targeting, and monetary targeting. In conclusion, the paper highlights the challenges that have been faced by the Indian economy and suggests enhancing the monetary policy's effectiveness and credibility in the era of dynamic domestic and global realities.